The case of the married woman : Caroline Norton and her fight for women's justice - Fraser, Antonia, 1932- (Pegasus Books, 2022)
Relates the story of nineteenth-century English poet Caroline Norton, who was denied access to her children by her husband after a sensational trial for adultery, and fought tirelessly for the rights of married women and mothers, resulting in the passage of the Infant Custody Act of 1839.